Immunomodulation From Moderate Exercise Promotes Control of Experimental Cutaneous Leishmaniasis - Terra, Rodrigo; Alves, Pedro J. F.; Lima, Ana K. C.; Gomes, Shayane M. R.; Rodrigues, Luciana S.; Salerno, Verônica P.; Da-Silva, Silvia A. G.; Dutra, Patricia M. L. (Frontiers in Cellular and Infection Microbiology, 2019)
ABSTRACT Physical exercise has been described as an important tool in the prevention and treatment of numerous diseases as it promotes a range of responses and adaptations in several biological systems, including the immune system. Studies on the effect of exercise on the immune system could play a critical role in improving public health. Current literature suggests that moderate intensity exercise can modulate the Th1/Th2 dichotomy directing the immune system to a Th1 cellular immune response, which favors the resolution of infections caused by intracellular microorganisms. Leishmaniasis is a group of diseases presenting a wide spectrum of clinical manifestations that range from self-limiting lesions to visceral injuries whose severity can lead to death. The etiological agents responsible for this group of diseases are protozoa of the genus Leishmania. Infections by the parasite Leishmania major in mice (Balb/c) provide a prototype model for the polarization of CD4+ T cell responses of both Th1 (resistance) or Th2 (susceptibility), which determines the progression of infections. The aim of this study was to evaluate the effect of exercise on the development of L. major experimental infections by scanning the pattern of immune response caused by exercise. Groups of Balb/c mice infected with L. major were divided into groups that performed a physical exercise of swimming three times a week or were sedentary along with treatment or not with the reference drug, meglumine antimoniate. Animals in groups submitted to physical exercise did not appear to develop lesions and presented a significantly lower parasite load independent of drug treatment. They also showed a positive delayed hypersensitivity response to a specific Leishmania antigen compared to control animals. The IFN-γ/IL-4 and IFN-γ/IL10 ratios in trained animals were clearly tilted to a Th1 response in lymph node cells. These data suggest that moderate intensity exercise is able to modulate the Th1 response that provides a protective effect against the development of leishmanial lesions.